Strengthening Meritocracy and Multidisciplinary Education: Preparing Youth for a Corruption-Free Indonesia Towards the 2045 Golden Era - Karismawati, Irma (Proceeding International Conference on Religion, Science and Education, 2025)
This research addresses the pressing need for a merit-based and morally grounded education system in Indonesia, particularly in the context of rampant nepotism and the placement of officials in sectors misaligned with their qualifications. Such practices contribute to an environment characterized by power tyranny and the distribution of positions based on personal connections rather than merit, undermining institutional efficiency and accountability. The current political landscape is marred by corruption and inefficiency, emphasizing the necessity for educational reform that prioritizes moral integrity and competence. By focusing on moral education and meritocracy, this study aims to cultivate a generation of youth equipped with integrity and ethical values, essential for combating corruption and enhancing the quality of human resources. As Indonesia approaches its demographic bonus era, the urgency for a well-prepared youth capable of contributing positively to society cannot be overstated. This paper explores innovative strategies for curriculum enhancement that integrate moral education and merit-based assessments, ensuring that students not only acquire knowledge but also develop a strong ethical foundation.Furthermore, the paper will present recommendations for policymakers and educational institutions to implement multidisciplinary approaches that promote collaboration and critical thinking. The findings will demonstrate that fostering a robust ethical framework in education can significantly contribute to creating a corruption-free Indonesia and ensuring sustainable development towards the 2045 Golden Era. Ultimately, this research highlights the vital role of education in shaping the future of the nation, advocating for systemic changes that align with the principles of meritocracy and moral responsibility.